Quantification and interpretation of postprandial whole-body protein metabolism using stable isotope methodology: a narrative review - Trommelen, Jorn; van Loon, Luc J. C. (Frontiers in Nutrition, 2024)
Stable isotopes are routinely applied to determine the impact of factors such as aging, disease, exercise, and feeding on whole-body protein metabolism. The most common approaches to quantify whole-body protein synthesis, breakdown, and oxidation rates and net protein balance are based on the quantification of plasma amino acid kinetics. In the postabsorptive state, plasma amino acid kinetics can easily be assessed using a constant infusion of one or more stable isotope labeled amino acid tracers. In the postprandial state, there is an exogenous, dietary protein-derived amino acid flux that needs to be accounted for. To accurately quantify both endogenous as well as exogenous (protein-derived) amino acid release in the circulation, the continuous tracer infusion method should be accompanied by the ingestion of intrinsically labeled protein. However, the production of labeled protein is too expensive and labor intensive for use in more routine research studies. Alternative approaches have either assumed that 100% of exogenous amino acids are released in the circulation or applied an estimated percentage based on protein digestibility. However, such estimations can introduce large artifacts in the assessment of whole-body protein metabolism. The preferred estimation approach is based on the extrapolation of intrinsically labeled protein-derived plasma bioavailability data obtained in a similar experimental design setting. Here, we provide reference data on exogenous plasma amino acid release that can be applied to allow a more accurate routine assessment of postprandial protein metabolism. More work in this area is needed to provide a more extensive reference data set.